Political Violence: A Typology - Ruggiero, Vincenzo (Kriminologijos studijos, 2018)
[full article, abstract in English; only abstract in Lithuanian] This paper offers a typology of different forms of political violence, linking them in a continuum and in an interdependent field of forces. The forms identified are systemic violence, institutional violence, group violence, armed struggle, terrorism and war. In the final section, after discussing how these types of violence influence one another, a strategy is suggested for their simultaneous reduction.